Lobular capillary hemangioma of the external auditory canal - (:unkn) unknown (MEDITERRANEAN SOC OTOLOGY & AUDIOLOGY, 2007)
Lobular capillary hemangiomas (LCHs, pyogenic granulomas) are benign, rapidly growing hemorrhagic lesions of unknown origin. Although an LCH is a common pathologic condition that can occur on the head and neck, the external auditory canal is an extremely rare site for the development of this tumor. Surgical resection is curative. We report the case of a 30-year-old woman treated for an LCH of the external auditory canal.